The Unionist Revolution in Turkey 1908 (Journal of the College of Basic Education, 2023)
Reform attempts in the Ottoman state go back to the era of Sultan Mahmud.The second (1808-1839), when he carried out a set of procedures that left clear effects on thecountry (1). The Ottoman politicians believed that the remedy for the deterioration in the Ottoman statelies in the movement to reform the system of governance and the Ottoman administration, as this resulted in what they calledB (organizations) in the year 1839, which extended in the opinion of many historians to the year 1908When the constitution was restored again.This movement began with the declaration of the reformist manifesto by Sultan Abd al-Majid 1839-1861.Known as (Sharif Kulkhana Line) in (2) 1839. Humayun's handwriting (3) 1856. And issuedNumerous decrees for serious reforms after that (4). However, these reforms were going awayIn vain, because it was impromptu and fleeting on the one hand, and because the European countries that were greedy for the Ottoman EmpireOn the other hand, it did not give it a chance to succeed, and because the Ottoman sultans, during these attempts,They were tyrannical and extravagant, so they did not adopt the desire for reform, adopting the perceptive and the sincere on the one handThird (5).